Why Not a Philosopher King? and Other Objections to Epistocracy - Kuljanin, Dragan (Phenomenology and Mind, 2019)
In this paper I will examine epistocracy as a form of limiting the political agency of some citizens (by removing their political rights) and offer an internal critique of it. I will argue that epistocracy runs into a number of logical and epistemic problems in trying to define who should be the members of an epistocratic polity. Furthermore, I will argue that the argument for epistocracy cannot ignore unjust background conditions. I will also suggest that some of the problems epistocracy attempts to correct can be solved in a more just way, while preserving democracy.